Immune enhancement of nitroreductase-induced cytotoxicity: studies using a bicistronic adenovirus vector. - Green, N; McNeish, I; Doshi, R; Searle, P; Kerr, D; Young, L (2003)
The nitroreductase (NR)/CB1954 enzyme prodrug system has given promising results in preclinical studies and is currently being assessed in phase I clinical trials. It is well established that there is an immune component to the bystander effect observed with other systems such as thymidine kinase and cytosine deaminase; however, such an effect has not previously been described using NR. We have preliminary data suggesting an immune bystander effect with NR to further examine these effects and their potential enhancement by cytokines, an adenoviral vector containing CMV-NR, an internal ribosome entry site (IRES) and the gene for murine GM-CSF (mGM-CSF) was constructed. The NR-GM-CSF virus was validated in 2 experimental models and demonstrated increased therapeutic efficacy in the MC26 murine colorectal tumour model. These data illustrate that the combination of suicide gene therapy using NR and CB1954 with immune stimulation via GM-CSF gives an improved response compared to either modality alone and suggests that the immune component of this response may be beneficial in combating unresectable, metastatic disease and preventing tumour recurrence.